Investigation of Negative Critical Points of the Characteristic Function for Problems with Nonlocal Boundary Conditions - Pečiulytė, S.; Štikonienė, O.; Štikonas, A. (Nonlinear Analysis: Modelling and Control, 2008)
In this paper the Sturm-Liouville problem with one classical and the other nonlocal two-point or integral boundary condition is investigated. Critical points of the characteristic function are analyzed. We investigate how distribution of the critical points depends on nonlocal boundary condition parameters. In the first part of this paper we investigate the case of negative critical points.
Keywords: Sturm-Liouville problem; nonlocal boundary condition; critical points